Konflik Kewenangan Sektoral Organisasi Perangkat Daerah dalam Pengelolan Penyakit Sosial Masyarakat di Kabupaten Karo - Ginting, Alung Brema; Noak, Piers Andreas; Erviantono, Tedi (Lenggogeni Data Publishing, 2024)
The Department of Social Affairs and the Karo Regency Civil Service Police Unit are responsible for handling female sex workers in Karo Regency. This research analyzes the extent of their authority in handling female sex workers and explores the conflict of authority between these two entities. The research method used is qualitative, relying on primary data from interviews and secondary sources from news articles. The study is grounded in Robin's (1996) theory and Rahim's (2001) conflict management theory. The analysis shows that the conflict of sectoral authority within regional apparatus organizations in managing social ills in Karo Regency operates effectively within existing authority and policies, promoting community security and order. However, the study finds that the Department of Social Affairs and the Karo Regency Civil Service Police Unit have not fully optimized their performance, focusing primarily on raids and patrols, with ongoing reports of female sex workers in Karo Regency.